A zero-field single-molecule magnet with luminescence thermometry capabilities containing soft donors. Issue 37 (30th June 2022) - Marin, Riccardo; Gálico, Diogo Alves; Gayfullina, Rezeda; Moilanen, Jani O.; Carlos, Luís D.; Jaque, Daniel; Murugesu, Muralee
Abstract : An investigation into the impact of soft donors on the optomagnetic and thermal sensing properties of lanthanide-based luminescent single-molecule magnets. Abstract : Simultaneous fine-tune of magnetic and optical properties in lanthanide single-molecule magnets (SMMs) is a daunting task. Even more so when additional functionalities, like luminescence thermometry, are sought after. Herein, we explore the use of a ligand with both soft and hard donor atoms (thiobenzoate, tba − ) as a strategy to prepare a multifunctional optomagnetic lanthanide complex. The proposed mononuclear Dy 3+ complex acts as a zero-field SMM, whose energy barrier to magnetization reversal was confirmed from the analysis of the photoluminescence spectrum. Moreover, the temperature dependence of the emission spectral profile was harnessed to build a thermometric approach working below 12 K – where the complex behaves as an SMM. In search for general trends informing the preparation of similar multifunctional SMMs, we modelled the electronic properties of a series of complexes where the sulfur atom of tba − is replaced for other chalcogens (O, Se, Te). These calculations show that careful choice of ligands with soft donor atoms can boost both magnetic and thermometric performances, paving the way for the rational design of novel multifunctional lanthanide complexes.